2022
DOI: 10.21203/rs.3.rs-1490969/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between body mass index and incidence of breast cancer in premenopausal women: A Japanese nationwide database study

Abstract: Purpose: The association between body mass index (BMI) and the incidence of premenopausal breast cancer in the Asian population remains unclear. We investigated this association using data from a Japanese nationwide administrative database.Methods: We retrospectively identified 785,703 females aged <45 years with available health checkup data on BMI from January 2005 and April 2020 from a Japanese nationwide database. Cox proportional hazards model was used to estimate hazard ratios for breast cancer (total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…In the current study, no relevant studies have reported the distribution characteristics of BMI, blood glucose and blood pressure in breast cancer patients. However, it has been pointed out that BMI can affect the occurrence, development and prognosis of breast cancer to a certain extent, or it is an independent risk factor for postoperative hyperlipidemia in patients with invasive breast cancer, and it is also closely related to the clinical characteristics of patients [12][13][14]. The reason for the failure to obtain consistent results in this study may be that only 26 patients (11.5%) with BMI ≥28 kg/m2 did not reach 15% of the total sample size, which resulted in insufficient confidence in the conclusions obtained and failed to find associations with patients' pathological characteristics and disease progression, so if we want to further substantiate this point of view, this study still needs a larger sample population to Therefore, in order to further confirm this idea, this study still needs a larger sample population for further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, no relevant studies have reported the distribution characteristics of BMI, blood glucose and blood pressure in breast cancer patients. However, it has been pointed out that BMI can affect the occurrence, development and prognosis of breast cancer to a certain extent, or it is an independent risk factor for postoperative hyperlipidemia in patients with invasive breast cancer, and it is also closely related to the clinical characteristics of patients [12][13][14]. The reason for the failure to obtain consistent results in this study may be that only 26 patients (11.5%) with BMI ≥28 kg/m2 did not reach 15% of the total sample size, which resulted in insufficient confidence in the conclusions obtained and failed to find associations with patients' pathological characteristics and disease progression, so if we want to further substantiate this point of view, this study still needs a larger sample population to Therefore, in order to further confirm this idea, this study still needs a larger sample population for further clarification.…”
Section: Discussionmentioning
confidence: 99%